2000
DOI: 10.1063/1.1312203
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of air-stable, low recombination velocity Si(111) surfaces through alkyl termination

Abstract: A two-step, chlorination/alkylation procedure has been used to convert the surface Si-H bonds on NH 4 F ͑aq͒ -etched ͑111͒-oriented Si wafers into Si-alkyl bonds of the form Si-C n H 2nϩ1 (nу1). The electrical properties of such functionalized surfaces were investigated under high-level and low-level injection conditions using a contactless rf apparatus. The charge carrier recombination velocities of the alkylated surfaces were Ͻ25 cm s Ϫ1 under high-level and low-level injection conditions, implying residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
315
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 206 publications
(332 citation statements)
references
References 21 publications
15
315
0
Order By: Relevance
“…4,5 Such surfaces have been shown to exhibit very low surface recombination velocities, indicating relatively few electrically active defect sites on the functionalized surface. 1,5 Consistently, no silicon oxides are detectable by surface-sensitive X-ray photoelectron spectroscopy on such initially prepared alkylated Si surfaces. 4,5 Although the rate of oxidation is significantly impeded, core-level photoelectron spectroscopy of the Si 2p region has shown that the alkylated Si(111) surfaces show small but detectable levels of oxide after several weeks of air exposure.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…4,5 Such surfaces have been shown to exhibit very low surface recombination velocities, indicating relatively few electrically active defect sites on the functionalized surface. 1,5 Consistently, no silicon oxides are detectable by surface-sensitive X-ray photoelectron spectroscopy on such initially prepared alkylated Si surfaces. 4,5 Although the rate of oxidation is significantly impeded, core-level photoelectron spectroscopy of the Si 2p region has shown that the alkylated Si(111) surfaces show small but detectable levels of oxide after several weeks of air exposure.…”
Section: Introductionmentioning
confidence: 72%
“…1,5 The chemical passivation is manifest as a very large suppression in the rate of oxide formation, with only a fraction of an equivalent monolayer formed after months in ambient air, as opposed to after minutes Figure 3. In the spectrum of the oxidized surface (b), the region above 1 eV is shown expanded 10× in signal intensity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations